Developement of Quantitative Analysis of Sparfloxacin by High Performance Liquid Chromatography - Rahman, Narun Nahar; Ahmad, Shahabuddin (Dhaka University Journal of Pharmaceutical Sciences, 2007)
An attempt has been made to develop a simple, sensitive and rapid high performance liquid chromatographic (HPLC) method of analysis for sparfloxacin using 35% acetonitrile in buffer solution as mobile phase. Buffer solution (40 mM of sodium dihydrogen phosphate in de-ionized water) was used as solvent to dissolve sparfloxacin and 0.05mg/ml stock solution was prepared. Sparfloxacin solution was scanned with UV-spectrophotometer and the absorption maximum (λmax) was found at 292 rim. This method was successfully applied to four tablet dosage forms of sparfloxacin encoded as ?, ?, ?, and ?, from four different companies and the result was found to be satisfactory and reproducible. Key words: Sparfloxacin, HPLC, analysis Dhaka Univ. J. Pharm. Sci. 6(1): 21-23, 2007 (June)The full text is of this article is available at the Dhaka Univ. J. Pharm. Sci. website